Analysis of The Safety and Efficacy of Different Types of Anesthesiological Support During Aesthetic Interventions For The Breast Glands In Ukraine: Life Sciences-Medicine - Kuchyn, Iurii; Sazhyn, Dmytro; Patlazhan, Gennadiy (International Journal of Life Science and Pharma Research, 2022)
In the prevailing era, mammoplasty is prevalent among women. Undeniable benefits of the method are the preservation of most anatomical structures and skin, and also better psychological status of patients after intervention. Hence, the present study intends to examine the features of aesthetic and reduction surgical interventions on the mammary glands in Ukraine. Materials and methods. The study was conducted by analyzing the inpatient ambulatory cards of 320 patients. Anesthesia was provided by propofol (n=130), sevoflurane (n=140) and combined use of sevoflurane and nalbuphine (n=50). The results of the study. It was found that usage of combined inhalation analgesia of sevoflurane with opioids was characterized by 41.9% less recovery time. It was found that 8 hours after surgery, the individual assessment of pain was lower in the group of combined analgesia with opioids relative to intravenous anesthesia with propofol (87.5%, p<0.05) and inhalation anesthesia with sevoflurane (71, 3%, p<0.05). After 24 hours all patients reported about pain below 1.0 point, however, in groups where sevoflurane and nalbuphine were used, the level of pain self-esteem was 2.61 and 3 times lower than after intravenous propofol. It was found that within 1 hour after surgery, the average cognitive score on the Montreal scale decreased in the group of intravenous propofol by 5.0% (p<0.05) and by 1.7% under inhalation anesthesia with sevoflurane. Under combined anesthesia the cognitive score remained at 12.0 points. The frequency of postoperative nausea was the highest level in the group of inhalation anesthesia - 16.7%. The addition of nalbuphine to sevoflurane significantly reduced the risk of postoperative nausea (? 2=7.250; p=0.007). Conclusions. Combined anesthesia with opioids is a highly effective anesthetic choice for aesthetic and reconstructive interventions on the mammary glands.